2020
DOI: 10.1111/are.14516
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Dimethyl sulfoxide (DMSO) and egg yolk on sperm motility, fertility and hatching rates of depikRasbora tawarensis(Pisces: Cyprinidae) eggs after short‐term cryopreservation

Abstract: Cryoprotectant is the crucial factor in the cryopreservation process. In general, there are two types of cryoprotectant, permeating and non‐permeating cryoprotectants. Dimethyl sulfoxide (DMSO) and egg yolk are common permeating and non‐permeating cryoprotectants respectively. Hence, the objective of the present study was to determine the best proportion of DMSO and egg yolk for the cryopreservation of Rasbora tawarensis sperm. A completely randomized experimental design was used in this study which involves t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 28 publications
1
15
0
Order By: Relevance
“…% DNA in tail 0.6 ± 0.1 a 0.7 ± 0.1 a 0.9 ± 0.1 a 0.9 ± 1.2 a 0.9 ± 1.2 a Tail moment (µ) 0.1 ± 0.0 a 0.1 ± 0.0 a 0.1 ± 0.0 a 0.1 ± 0.0 a 0.1 ± 0.0 a The present study revealed that extender-3 was not suitable for the cryopreservation of marbled flounder sperm. However, it has been previously reported that extender-3 is suitable for cryopreserving sperm of Rasbora tawarensis (Muchlisin et al, 2020) and yellow catfish, Pelteobagrus fulvidraco (Pan et al, 2008). The present findings suggest that the absence of sugar in extender-3 might be responsible for the reduced motility of postthaw sperm, although a positive impact of sugar-based extenders (extender-1 and extender-2) on the sperm cryopreservation has been described in the previous section because such extender can additionally act as a non-penetrating CPA (Rusco et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…% DNA in tail 0.6 ± 0.1 a 0.7 ± 0.1 a 0.9 ± 0.1 a 0.9 ± 1.2 a 0.9 ± 1.2 a Tail moment (µ) 0.1 ± 0.0 a 0.1 ± 0.0 a 0.1 ± 0.0 a 0.1 ± 0.0 a 0.1 ± 0.0 a The present study revealed that extender-3 was not suitable for the cryopreservation of marbled flounder sperm. However, it has been previously reported that extender-3 is suitable for cryopreserving sperm of Rasbora tawarensis (Muchlisin et al, 2020) and yellow catfish, Pelteobagrus fulvidraco (Pan et al, 2008). The present findings suggest that the absence of sugar in extender-3 might be responsible for the reduced motility of postthaw sperm, although a positive impact of sugar-based extenders (extender-1 and extender-2) on the sperm cryopreservation has been described in the previous section because such extender can additionally act as a non-penetrating CPA (Rusco et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Thus, the fresh sperm were characterized based on pH, color, and consistency, and also for initial quality (motility and viability). Also, only sperm with minimum motility above 60% were used for cryopreservation (Muchlisin et al, 2020).…”
Section: Broodfish Domestication and Sperm Collectionmentioning
confidence: 99%
“…In cryopreservation, cryoprotective agent (CPA) is known to play an important role during this process, and therefore, it must be known which type of CP is suitable for species to species, this is because the CPA is species dependent (Chao & Liao, 2001;Sarder et al, 2012). There are generally two types of CPA, intracellular (ICPA) and extracellular (ECPA) (Muchlisin, 2005;Muchlisin et al, 2020). The ICPA possesses the capacity to penetrate sperm cells and confer internal protection through the formation of ice crystals, while the latter confers an external shield from temperature shock, both during cryopreservation and thawing (Muchlisin et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations